(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The present study, aimed at determining the level of resilience of a country, identified the effects of the health crisis as a form of external shock on the impact relationship between vulnerability and economic growth. Using a macroeconomic perspective, we conducted panel data estimates on a sample of countries classified by level of vulnerability (high, medium, and low) using the FGLS method for panel data with cross-sectional and serial correlation over the period 2000-2021.